"A Powerful Tool": A Phenomenological Study of School Counselors' Experiences with Social Stories. (2016) - Goodman-Scott, Emily; Carlisle, Robert; Clark, Madeline; Burgess, Melanie
Social stories are an evidence-based practice used to address students' social skills. Current literature primarily addresses special education teachers' use of social stories when working with youth with autism spectrum disorder. Although school counselors meet students' social/emotional needs, little research exists documenting their experiences with social stories. This phenomenological study examined the lived experiences of school counselors using social stories (N = 12). The authors found that school counselors experienced social stories as a powerful process and encountered obstacles to social story use, and that social stories fit within the role of school counselors, including running a comprehensive school counseling program.